Pengaruh Kualitas Pelayanan, Persepsi Harga dan Lokasi terhadap Kepuasan Konsumen di Apotek Jadi Farma Kabupaten Pidie Jaya - Roza, Ida; Kamaruddin, Kamaruddin (Aceh Cooperative Care, 2023)
The research aims to analyze the partial and simultaneous influence of service quality factors, price perceptions and location on consumer satisfaction at Jadi Farma Pharmacy in Pidie Jaya Regency. Data was obtained through a questionnaire based on the perceptions of a sample of 45 respondents, namely permanent consumers of Jadi Farma Pharmacy. The analysis method used is the path analysis approach. The research results show that the influence of service quality, price perception and location on consumer satisfaction is proven through a path model with the formula Y = 0.176 X1 + 0.242 X2 + 0.275 X3. This means that simultaneously these three factors have a positive influence with a contribution of 71.5% to consumer satisfaction. Partially, the direct and indirect influence of service quality factors on consumer satisfaction is 21,4%. The direct and indirect influence of price on satisfaction is 21,72%. Meanwhile, the direct and indirect influence of apatek location aspects on satisfaction is 26,37%.